COVID-19 testing, infection, and vaccination among deported Mexican migrants: Results from a survey on the Mexico-U.S. border - Martínez-Donate, Ana P.; Correa-Salazar, Catalina; Bakely, Leah; González-Fagoaga, Jesús Eduardo; Asadi-Gonzalez, Ahmed; Lazo, Mariana; Parrado, Emilio; Zhang, Xiao; Rangel Gomez, Maria Gudelia (Frontiers in Public Health, 2022)
Background: Migration is a structural determinant of health. Migrants, ethnic, racial minorities, and individuals held in congregate settings have been disproportionately impacted by the COVID-19 pandemic. Migrants detained and held in immigration and other detention settings in the U.S. have faced increased risk for COVID-19 infection, but data on this population is scarce. This study sought to estimate rates of COVID-19 testing, infection, care seeking, and vaccination among Mexican migrants detained by U.S. immigration authorities and forcibly returned to Mexico. Methods: We conducted a cross-sectional probability survey of Mexican migrants deported from the U.S. to three Mexican border cities: Tijuana, Ciudad Juárez, and Matamoros (N=306). Deported migrants were recruited at Mexican migration facilities after being processed and cleared for departure. Survey measures included self-reported history of COVID-19 testing, infection, care seeking, vaccination, intentions to vaccinate, and other prevention and risk factors. Weighted data were used to estimate population-level prevalence rates. Bivariate tests and adjusted logistic regression models were estimated to identify associations between these COVID-19 outcomes and demographic, migration, and contextual factors. Results: About 84.1% of migrants were tested for COVID-19, close to a third were estimated to have been infected, and, among them, 63% had sought care for COVID-19. An estimated 70.1% had been vaccinated against COVID-19 and, among those not yet vaccinated, 32.5% intended to get vaccinated. Close to half (44.3%) of respondents had endured crowdedness while in detention in the U.S. Socio-demographic (e.g. age, education, English fluency), migration (e.g. type of detention facility, time in detention), and contextual variables (i.e. survey city and survey quarter) were significantly related to COVID-19 testing, infection, care seeking, and vaccination history. Conclusion: These findings are evidence of increased risk for COVID-19 infection, insufficient access to testing and treatment, and missed opportunities for vaccination among Mexican migrants detained in and deported from the U.S. While we contend with the uncertainty of the next waves of the pandemic, decarceration and other measures informed by public health principles must be implemented to reduce COVID-19 risk and increase access to prevention, diagnostic, and treatment services among this underserved population.